Exogenous Bimodal Cues Attenuate Age-Related Audiovisual Integration. (May 2021) - Ren, Yanna; Zhang, Ying; Hou, Yawei; Li, Junyuan; Bi, Junhao; Yang, Weiping
Previous studies have demonstrated that exogenous attention decreases audiovisual integration (AVI); however, whether the AVI is different when exogenous attention is elicited by bimodal and unimodal cues and its aging effect remain unclear. To clarify this matter, 20 older adults and 20 younger adults were recruited to conduct an auditory/visual discrimination task following bimodal audiovisual cues or unimodal auditory/visual cues. The results showed that the response to all stimulus types was faster in younger adults compared with older adults, and the response was faster when responding to audiovisual stimuli compared with auditory or visual stimuli. Analysis using the race model revealed that the AVI was lower in the exogenous-cue conditions compared with the no-cue condition for both older and younger adults. The AVI was observed in all exogenous-cue conditions for the younger adults (visual cue > auditory cue > audiovisual cue); however, for older adults, the AVI was only found in the visual-cue condition. In addition, the AVI was lower in older adults compared to younger adults under no- and visual-cue conditions. These results suggested that exogenous attention decreased the AVI, and the AVI was lower in exogenous attention elicited by bimodal-cue than by unimodal-cue conditions. In addition, the AVI was reduced for older adults compared with younger adults under exogenous attention.